Recent Advances Regarding the Physiological Functions and Biosynthesis of D-Allulose - Chen, Zhou; Gao, Xiao-Dong; Li, Zijie (Frontiers in Microbiology, 2022)
D-Allulose, a generally regarded as safe (GRAS) sugar, is rare in nature. It is among the most promising sweeteners for future use due to its low caloric content, sucrose-like taste and unique functions. D-Allulose has many physiological effects, such as antiobesity, antihyperglycemia, antidiabetes, anti-inflammatory, antioxidant and neuroprotective effects. Therefore, D-allulose has important application value in the food, pharmaceutical and health care industries. However, the high cost of D-allulose production limits its large-scale application. Currently, biotransformation is very attractive for D-allulose synthesis, with the two main methods of biosynthesis being the Izumoring strategy and the DHAP-dependent aldolase strategy. This article reviews recent advances regarding the physiological functions and biosynthesis of D-allulose. In addition, future perspectives on the production of D-allulose are presented.